Narasi Kesetiaan demi Keutuhan Rumah Tangga dalam dalam Sastra Bali: Analisis “Geguritan Saci” - Ni Nyoman Karmini (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
Literary works usually convey social messages throughthe story and the reader should interpret the meaningbehind the symbols and metaphore in the story. This articleanalyzes a traditional Balinese literature of poetic genre,Geguritan Saci (The Song of Saci), which is rich in symbolsand methaphore of Balinese local wisdom. By using themethod of interpretation, this article discovered that thereare at leastsix good character who symbolized in this story,namely, respect, responsible, good citizens, fair, caring, andtrusthworthy. Based on these findings, this article suggeststhat the values contained in this poetic work should be readand disseminated to the society at large.